Lanadelumab in a kidney transplant patient with hereditary angioedema due to C1-inhibitor deficiency and high cardiovascular risk - a case report - Gidaro, Antonio; La Cava, Leyla; Donadoni, Mattia; Popescu Janu, Valentina; Cogliati, Chiara; Brucato, Antonio Luca; Zanichelli, Andrea; Cancian, Mauro; Bizzi, Emanuele (Frontiers in Immunology, 2024)
Introduction: Cardiovascular pathologies represent the first cause of death in uremic patients and are among the leading causes of mortality in patients with hereditary angioedema due to C1inhibitor deficiency (HAE-C1INH). Before 2020, the most common treatment for long-term prophylaxis in HAE-C1INH patients in Italy was attenuated androgen, which may increase cardiovascular risk by multiple mechanisms.We present a case report of a 56-year-old patient with HAE-C1INH type I affected by IgA nephropathy with severe kidney impairment. The patient experienced a first kidney transplant and, after late rejection, underwent a second kidney transplant. Further comorbidities included obesity, hypertensive cardiomyopathy, HCV liver disease, and dyslipidemia. His prophylactic therapy to prevent angioedema attacks had consisted of attenuated androgens for about 40 years. Since 2020, new modern targeted therapy for LTP, particularly lanadelumab, has shown promising results. The majority of patients with attenuated androgens have been successfully switched to lanadelumab, including our patient. Since introducing lanadelumab (300 mg subcutaneously every two weeks; after a six-month attack-free period, the dosing interval of lanadelumab was extended to four weeks), the patient has not experienced any acute HAE attack and did not report any adverse events. Moreover, we observed decreased total cholesterol, C-LDL, and body mass index, reducing the Matsushita et al. score for ten years of cardiovascular risk from 13.2% to 9.3%.lanadelumab is effective and safe in preventing hereditary angioedema attacks, as well as in reducing cardiovascular risk in an immunosuppressed patient with significant comorbidities.The successful outcomes of this case highlight the potential of lanadelumab as a promising prophylactic therapy.